Hormonal Contraceptives and Athletic Outcomes - analysis of potential effects of oral contraceptives on strength, endurance, mood, and overall competitive results - Dominika Lewandowska; Dominika Rosińska-Lewandoska; Dominika Strep; Anna Podraza; Julia Grabowska; Maciej Kwiatkowski; Patryk Romańczyk; Julia Białczak; Weronika Kanownik; Jakub Rosiński (Journal of Education, Health and Sport)
Introduction